A novel instrumented projectile for investigation of impact dynamics - Pang, Xin (2017)
Instrumented projectiles are widely used in the arena of military, geological studies, planetary and comet mission. Their applications in harsh environments call for a rugged and highly reliable system to ensure the survival of the internal electronics and reliable measurement of in situ data. These data are essential to study the various properties of the penetrated target and the projectile. The design, development and construction of a novel instrumented projectile for in situ deceleration measurement in high velocity impact conditions are presented in this thesis. A series of impact tests were performed using the developed instrumented projectile. The obtained acceleration responses from the series of tests, composed of transient, vibration and rigid-body responses were studied using frequency and frequency-time analysis to deduce the dominant resonance frequency of the instrumented projectile. Based on this deduction, optimum parameters for the design of the digital low-pass filtering schemes are obtained, which subsequently provides a consistent framework for the remaining studies in this work to extract the rigid-body deceleration of the instrumented projectile. The rigid body deceleration profile is important for examining the resistance of targets and verifying various prediction models. The novel instrumented projectile was employed to study the resistance characteristics of closed-cell aluminium foams of two different density groups and gauge lengths. The study shows that inertia effect has a larger influence on the rate sensitivity of the low density foams compared with the high density foams. This study also shows that the strain hardening behaviour of foam specimens and the normalised penetration depth are important factors that dictate the deceleration response profile of the projectile. The abovementioned factors are important to design an efficient energy absorber that controls the deceleration profile of a colliding mass. An analytical model is proposed to predict the responses of instrumented projectile when it is impacting on closed-cell aluminium foams. Predictions by the models are compared with experimental data and with the results obtained from three-dimensional finite element simulations. This proposed model is based on an exponential stress-strain relation that takes into consideration of the strain-hardening behaviour of the aluminium foam specimens. It was found that the proposed model gives a better prediction than another earlier model that is based on a Rigid Perfectly-Plastic Locking idealisation that dictates the foam’s resistance, which is only able to approximate the stress-strain characteristic of metal foams with low strain hardening.